ANALISIS USAHATANI BERKELANJUTAN PADA RUMAHTANGGA TANI DI DAERAH LAHAN PASANG SURUT KALIMANTAN TENGAH - Wardie, Jhon; Hartono, Slamet; Darwanto, Dwidjono Hadi; Irham, . (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
This research is aimed to analyse level income and level farm sustainability at farm household in tidal swamps area Central Kalimantan. This research location, i.e., Kapuas regency is selected purposively and 100 samples are sampled purposively on the basis of two difference farming locations of tidal swamps area that managed by local farm households and non local farm households. Level farm household income then analysed with tabulate from whole activity. Analysis to indicate the difference level of farm household income between local and non local farm household use t-test. . The farm sustainability is analysed with indicator skoring farm sustainability. The research showed that there is no significant difference between local and non local farm household income statistically eventhough local farm household income is higher than that of non local. The research also revealed that level farm sustainability of non local farm household is categorized as high sustainable, while local farm household is categorized into moderate. Result from t-test indicates a significant difference of sustainability index value between two farm households. . Furthermore, Farm households have right motivation and apply sustainable agriculture principles which is emphasized to take care of environmental continuity of natural resources without neglecting in increasing of productivity and income. In terms of external and internal input usage, non local farm household behavior and attitudes is better than local farm household.Keywords: tidal swampsarea, farm household, sustainable farming, external input